Will Rogers and Sally Eilers at First Poly Royal in 1933 (1933)
On back: 'Left to right: Julian A. McPhee, Will Rogers, Sally Eilers, and Henry King, director of "State Fair". Mr. Cooper - Sorry the pig moved out of these shots. We have no negatives of the group which also caught Blue Boy. Maybe they can make a compound.'